Sex estimation from reconstructed scapula models using discriminant function analysis in the Malaysian population - Omar, N; Ali, SHM; Shafie, MS; Ismail, NAN; Hadi, H; Ismail, R; Nor, FM (Taylor & Francis Ltd, 2024)
Indexed by SCOPUS/ERA